Empirical modeling of the relationship between decision sight distance and stopping sight distance based on AASHTO - Shy BASSAN (Archives of Transport, 2018)
The paper introduces implementation of highways' stopping sight distance (SSD) and decision sight distance (DSD) based on AASHTO modeling assumptions. SSD characterizes the necessary distance for highway vehicles to stop safely in front from an obstacle. SSD is a function of vehicle speed, perception reaction time, deceleration rate, and grade based on AASHTO and most highway design international guidelines. The deceleration rate which is assumed constant (3.4 m/sec2) based on AASHTO 2011 is generally controlled by the friction coefficient depending on the road surface conditions. A driver's demanded deceleration rate may not exceed the range of friction coefficient according to various pavement conditions. Although SSD is generally sufficient to allow skilled and alert drivers to the stop their vehicles under regular situations, this distance is insufficient when information is difficult to comprehend. A DSD should be provided in highways geometric design when the driver is required to detect an unexpected or difficult to perceive information source. Interchanges (specifically exit ramps) and intersections, and required changing in driver direction of travel, changes in the basic cross section such as toll plaza, lane drop, are typical scenarios where driver needs DSD in the safety manner. The introduction of the two sight distance types (SSD and DSD) is a perquisite for empirical modeling of the relationship between DSD and SSD. The modeling refers to DSD for rural highways, suburban roads, and urban roads based on AASHTO models. Specifically the paper covers DSD three avoidance maneuver types of stopping (types A, A1, B) and three maneuver types of speed, path, and direction changing (types C,D, E) for the three roadway categories. The major parameters that control these avoidance types are pre-maneuver times, and pre-maneuver plus maneuver times. The empirical relationship proposed in this study simplifies the process of evaluating the decision sight distance based on stopping sight distance record, based on AASHTO models, without the need of strenuous estimation of the DSD model maneuver and deceleration parameters. Such a simplified correlation has not been found in the literature except a rough approximation documented in the British highway design guidelines.